20Forest loss shapes the landscape suitability of Kyasanur Forest disease in the Western Ghats, India. (2nd September 2021) - Walsh, Michael; Mor, Siobhan; Maity, Hindol; Hossain, Shah
Abstract: Background: Anthropogenic pressure in biodiversity hotspots is increasingly recognised as a major driver of the spillover and expansion of zoonotic disease. In the Western Ghats region of India, a devastating tick-borne zoonosis, Kyasanur Forest disease (KFD), has been expanding rapidly beyond its endemic range in recent decades. While it has been suggested that anthropogenic pressure in the form of land use changes that lead to the loss of native forest may be directly contributing to the expanding range of KFD, clear evidence has not yet established the association between forest loss and KFD risk. Methods: The current study sought to investigate the relationship between KFD landscape suitability and both forest loss and mammalian species richness to inform its epidemiology and infection ecology. Forty-seven outbreaks of KFD between 1 January, 2012 and 30 June, 2019 were modelled as an inhomogeneous Poisson process. Results: Both forest loss (relative risk (RR) = 1.83; 95% C.I. 1.33 – 2.51) and mammalian species richness (RR = 1.29; 95% C.I. 1.16 – 1.42) were strongly associated with increased risk of KFD. Conclusions: These results provide the first evidence of a clear association between increasing forest loss and risk for KFD. Moreover, the findings also highlight the importance of forest loss in areas of high biodiversity. This evidence supports integrative approaches to public health that incorporate conservation strategies simultaneously protective of humans, animals, and the environment. Key messages: The association between deforestation and KFD risk suggest potential benefit in leveraging conservation efforts in the service of public health.